Tinjauan Yuridis Peraturan Wali Kota Cirebon Nomor 5 Tahun 2022 Tentang Pengendalian Penggunaan Kantong Plastik di Kota Cirebon - Ayu Dysa Nurjanah; Achmad Kholik (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
Plastic waste has become a persistent environmental problem because of its high consumption, slow degradation, and potential impacts on ecosystems and public health. This study analyzes the legal design and effectiveness of Cirebon Mayor Regulation Number 5 of 2022 concerning the Control of Plastic Bag Use. It employs empirical legal research with statutory, conceptual, and sociological approaches. Primary data derive from field observations and information concerning the implementation of the regulation in modern retail establishments, while secondary data consist of legislation, government documents, and scholarly literature on waste governance, environmental law, legal awareness, and plastic reduction. The data are qualitatively analyzed through legal substance, institutional implementation, target coverage, enforcement, public participation, and environmental outcomes. The findings show that the regulation has a valid legal basis and contains obligations concerning planning, education, business compliance, supervision, community participation, and administrative sanctions. Nevertheless, implementation remains suboptimal. The regulation mainly targets shopping centers and modern stores, while traditional shops and informal retailers remain outside its effective reach. Administrative sanctions are relatively weak, supervision is not systematic, and the use of environmentally friendly alternatives has not necessarily reduced total plastic waste. The study argues that effective plastic control requires broader regulatory coverage, measurable reduction targets, stronger monitoring, incentives and disincentives, extended producer responsibility, reusable packaging, public education, and periodic evaluation based on waste data.